Expansion of higher education and time-consistent taxation - Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyzes educational choices and political support for subsidies to higher education in the presence of a time-consistency problem in income redistribution. There may be political support for so generous subsidization that it motivates the median voter to obtain higher education. As a result of increasing own income, the median voter prefers in the future lower taxes than without higher education. Therefore, the expansion of participation in higher education during the second half of the 20th century may have partly been driven by the aim to limit the political support for overly generous income redistribution.
Keywords: H52; I22; D72; 330; Hochschule; Bildungsverhalten; Einkommensumverteilung; Zeitkonsistenz; Median Voter; Bildungspolitik; Steuer; Theorie